Hamas Attacks, Israel Bombs Gaza and Misinformation Surges Online - Bellingcat Investigation Team (bellingcat, 2023)
Videos supposedly from the latest escalation of the conflict are actually years old, from the wrong country or don’t depict a warzone at all.
Western Asia
Keywords: 2023-10 October